2004
DOI: 10.1007/s00439-004-1186-7
|View full text |Cite
|
Sign up to set email alerts
|

Mutational analysis of OGG1, MYH, MTH1 in FAP, HNPCC and sporadic colorectal cancer patients: R154H OGG1 polymorphism is associated with sporadic colorectal cancer patients

Abstract: MYH, OGG1 and MTH1 are members of base excision repair (BER) families, and MYH germline mutations were recently identified in patients with multiple adenomas or familial adenomatous polyposis (FAP). A total of 20 APC-negative Korean FAP patients were analyzed for OGG1, MYH and MTH1 germline mutations. A total of 19 hereditary nonpolyposis colorectal cancer (HNPCC), 86 suspected HNPCC, and 246 sporadic colorectal cancer cases were investigated for OGG1 and MYH mutations. A total of 14 R154H OGG1 polymorphisms w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
33
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 20 publications
3
33
0
1
Order By: Relevance
“…The MYH mutations in the AFAP families, which are frequently observed among Caucasians (Y165C and G382D) or other races of Indian (E466X) and Pakistani (Y90X), were not identified in our study. This finding is similar to other studies involving Korean, Japanese, and Jewish populations [15,19,25], and indicates a marked ethnic or regional segregation in MYH polyposis. However, we found two novel heterozygous MYH mutations: R170Q and A359V.…”
Section: Discussionsupporting
confidence: 92%
“…The MYH mutations in the AFAP families, which are frequently observed among Caucasians (Y165C and G382D) or other races of Indian (E466X) and Pakistani (Y90X), were not identified in our study. This finding is similar to other studies involving Korean, Japanese, and Jewish populations [15,19,25], and indicates a marked ethnic or regional segregation in MYH polyposis. However, we found two novel heterozygous MYH mutations: R170Q and A359V.…”
Section: Discussionsupporting
confidence: 92%
“…These findings suggest that constitutive activation of the Wnt canonical pathway contributes to human carcinogenesis [6]. However, somatic mutations in APC and β-catenin genes have been only rarely detected in Korean patients with colorectal cancer [7]. Thus, it is likely that there are other mechanisms responsible for activating the Wnt signaling pathway in the development of sporadic colorectal cancer in Korean patients.…”
mentioning
confidence: 85%
“…(13-18) However, neither of these two variants has ever been detected in East Asians, including Japanese, (19)(20)(21)(22) suggesting that they are ethnicity-specific alleles. Based on the above findings, we hypothesized that MUTYH variants other than Y165C and G382D act as low-penetrance susceptibility alleles in Japanese CRC, similar to a situation previously reported for the APC and CHEK2 gene variants.…”
mentioning
confidence: 99%
“…(8,9,11,12) The frequencies of Y165C and G382D have been investigated in several colorectal cancer (CRC) case-control studies, and monoallelic carriers of these variants were found in 0.0 -2.6% of the cases and 0.0 -2.1% of the controls and biallelic carriers of these variants were found in 0.0-0.8% of the cases and 0% of the controls, respectively. (13)(14)(15)(16)(17)(18) However, neither of these two variants has ever been detected in East Asians, including Japanese, (19)(20)(21)(22) suggesting that they are ethnicity-specific alleles. Based on the above findings, we hypothesized that MUTYH variants other than Y165C and G382D act as low-penetrance susceptibility alleles in Japanese CRC, similar to a situation previously reported for the APC and CHEK2 gene variants.…”
mentioning
confidence: 99%